An Accurate Performance Analysis of Hybrid Efficient and Reliable MAC Protocol in VANET under Non-saturated Conditions - Akram A. Almohammedi; Nor K. Noordin; A. Sali; Fazirulhisyam Hashim; Abdulmalek Al-Hemyari (Institute of Advanced Engineering and Science, 2017)
Vehicular Ad Hoc Networks (VANETs) is a technology supporting two types of applications, safety and service applications with higher and lower priorities respectively. Thereby, Medium Access Control (MAC) protocol is designed to provide reliable and efficient data broadcasting based on prioritization. Different from the IEEE 1609.4 (legacy), HER-MAC protocol is a new multi-channel MAC proposed for VANETs, offering remarkable performance with regards to safety applications transmission. This paper focuses on the analysis of packet delivery ratio of the HER-MAC protocol under non-saturated conditions. 1-D and 2-D Markov chains have been developed for safety and non-safety applications respectively, to evaluate mathematically the performance of HER-MAC protocol. The presented work has taken into account the freezing of the backoff timer for both applications and the backoff stages along with short retry limit for non-safety applications in order to meet the IEEE 802.11p specifications. It highlights that taking these elements into consideration are important in modeling the system, to provide an accurate estimation of the channel access, and guarantees that no packet is served indefinitely. More precise results of the system packet delivery ratio have been yield. The probability of successful transmission and collisions were derived and used to compute the packet delivery ratio. The simulation results validate the analytical results of our models and indicate that the performance of our models outperformed the existing models in terms of the packet delivery ratio under different number of vehicles and contention window.